Transformation of the Sea Terminal in Gdynia into the Museum of Emigration - Hirsch, Robert (Protection of Cultural Heritage, 2020)
The article concerns the adaptation of the historic Gdynia Sea Terminal into the Emigration Museum. The building was designed and built in the 1930s and is an outstanding work of modernist architecture. The building is located on an artificial pier of a marine harbour. It was used to handle passenger and cargo traffic sailing to, among others, New York. In 1943 the building was partially destroyed during an air raid and was not fully rebuilt. After World War II the building served various purposes, but has not regained its former glory. In 2012 the idea of creating an Emigration Museum in Gdynia was born. The conceptual design assumed reconstruction, in modern form, of parts of the building destroyed during the war and reconstruction of the interior design. The museum opened in 2016, and the following year the project was awarded the main prize of the Minister of Culture and National Heritage in the competition "Monument well taken care of".